Substantiation of directions for improving the management mechanism of the construction complex in the Donetsk People’s Republic - A. S. Tarasov (Вестник университета, 2025)
The relevance of the study of management mechanisms of the construction complex is due to its fundamental role in the economic development and structural transformations of the national economy.   The construction complex acts not only as a producer of material goods, but also as a catalyst for economic growth, creating a multiplier effect in related industries and stimulating innovative activity. In a dynamically changing market environment characterised by high volatility of supply and demand as well as by an accelerated pace of technological innovation, improving management approaches in the construction industry becomes critically important. In addition, modern imperatives of sustainable development, including environmental, social and economic aspects, require a revision of traditional management models and introduction of innovative strategies. This article is aimed at a comprehensive analysis and scientific justification of the directions of optimisation of the management mechanism of the construction complex.   The aim of the research is to develop an integrated management approach that will increase competitiveness of the industry at the national and international levels, ensure long-term economic efficiency and sustainability in the face of global challenges.   Special attention is paid to the analysis of innovative management practices, digitalisation of management processes, and adaptation of international experience to the Russian realities.